Armenian Studies in Middle East Studies: Internationalism and Solidarity. (August 2022) - Shirinian, Tamar
Abstract : In thinking about the prompt for this forum—on the ways in which Armenia and Armenians sit within Middle East studies and the ways in which they are often occluded from the sights of Middle East studies—what comes to mind is the critical necessity for internationalism and solidarity. This might at first seem only tangentially or indirectly relevant to the object of investigation here; after all, we are talking about geography, history, and facts. However, I think that it is relevant to how (as in with what sense, orientation, and from what perspective) we approach the question of scholarly regional belonging. Like any topic of intellectual inquiry, how we imagine and define regions has implications on what we find in those regions: the sites of importance and focus; the connections between different groups, persons, and events; and the scope of investigations. Internationalism and solidarity as frameworks for understanding Armenia and Armenians as a part of the Middle East orient us to the region by way of connections to the various peoples of that region with a political and ideological commitment to the well-being of all peoples there and everywhere. Many of the commentaries in this forum focus on the marginalization of particular minorities in Middle East Studies (Armenians, Copts, and Assyrians in this forum, and we also could think about the marginalization of Kurds and other minoritized populations in the region). 1 This in itself is a critical and necessary point of departure. I would like to approach the question from another angle, however. How might we think about this problem from the other side? How does Armenian studies see itself in connection with Middle East studies? Here, although I recognize that Armenian studies is a changing field and is not monolithic, with various differences between the field as it developed in Europe and the United States and that which developed in the Republic of Armenia, there are a few continuities that I would like to problematize and imagine differently. What might the future of Armenian studies be if it were made through politically committed questions, articulations, and collaborations? How might this produce a (different) sense of belonging to Middle East studies?